Association between Internet use and depression among older adults in China: the chain-mediating role of volunteer activity participation and friend network - Liu, Yujiang; Li, Fang; Sun, Jian (Frontiers in Public Health, 2024)
Background Depression is a significant burden on individuals and society, which requires our attention and action. As the aging wave collides with digitalization, further research is needed to understand how internet use relates to depression in older adults. This study aimed to investigate whether volunteer activity participation and friend networks played a chain mediating role in this relationship from the perspective of the socioemotional selectivity theory. Method This study’s data was derived from the 2018 China Longitudinal Aging Social Survey (CLASS), comprising 5,558 samples. The study employed the OLS model for benchmark regression and multiple robust check methods, including altering variable settings and utilizing the instrumental variable model. In addition, the generalized structural equation model (GSEM) was used to analyze the mechanism. Result Using the internet was significantly associated with reduced depression in older adults (coefficient = −0.9321, p < 0.001). The instrumental variable model confirmed this reduction (coefficient = −0.9200, p < 0.001). Moreover, we found that there were three indirect pathways of Internet use on depression among older adults: the mediating role of volunteer activity participation (all p-values <0.001), the mediating role of friend network (all p-values <0.001), and the chain mediating role of both factors (all p-values <0.001). Conclusion Based on the research findings, we suggest mobilizing tech-savvy older adults to assist others in adopting digital technology and using the internet. We also suggest that the government could assist in creating older adult-friendly communities. Social workers could collaborate with tech-savvy older adults to organize various voluntary activities, encouraging more senior citizens to participate. In addition, we recommend that the community should consider the form of activities to help older adults make friends first rather than solely focusing on voluntary activities.